Efficacy of Teicoplanin-Gentamicin Given Once a Day on the Basis of Pharmacokinetics in Humans for Treatment of Enterococcal Experimental Endocarditis - López, Pedro (American Society for Microbiology, 2001)
With the aim of investigating home therapy for enterococcal endocarditis, we compared the efficacy of teicoplanin combined with gentamicin given once a day or in three daily doses (t.i.d.) with the standard treatment, ampicillin plus gentamicin administered t.i.d., for treating experimental enterococcal endocarditis. The antibiotics were administered by using “human-like pharmacokinetics” (H-L), i.e, pharmacokinetics like those in humans, that simulated the profiles of these drugs in human serum. Animals with catheter-induced endocarditis were infected intravenously with 10(8) CFU of Enterococcus faecalis EF91 (MICs and MBCs of ampicillin, gentamicin, and teicoplanin, 0.5 and 32, 16 and 32, and 0.5 and 1 μg/ml, respectively) and were treated for 3 days with ampicillin H-L at 2 g every 4 h plus gentamicin H-L at 1 mg/kg every 8 h, or teicoplanin H-L at 10 mg/kg every 24 h, alone or combined with gentamicin, administered at dose of H-L at 1 mg/kg every 8 h or H-L at 4.5 mg/kg every 24 h. The results of therapy for experimental endocarditis due to EF91 showed that teicoplanin alone was as effective as ampicillin alone in reducing the bacterial load (P > 0.05). The combination of ampicillin or teicoplanin with gentamicin was more effective than the administration of both drugs alone in reducing the log(10)CFU/gram of aortic vegetation (P < 0.01 and P < 0.05, respectively). Teicoplanin plus gentamicin H-L at 4.5 mg/kg, both administered every 24 h, showed an efficacy equal to the “gold standard,” ampicillin plus gentamicin H-L at 1 mg/kg t.i.d. (P > 0.05). Increasing the interval of administration of gentamicin to a single daily dose combined with teicoplanin resulted in a reduction of bacteria in the vegetations equivalent to that achieved with the recommended regimen of ampicillin plus thrice-daily gentamicin in the treatment of experimental endocarditis due to E. faecalis. Teicoplanin plus gentamicin, both administered once a day, may be useful home therapy for selected cases of enterococcal endocarditis.